Measurement Model for Determining the Disparity Factors of Intercity Railway Transportation - Kestsirin Theerathitichaipa; Panuwat Wisutwattanasak; Chinnakrit Banyong; Manlika Seefong; Sajjakaj Jomnonkwao; Thanapong Champahom; Vatanavongs Ratanavaraha; Rattanaporn Kasemsri (Salehan Institute of Higher Education, 2024)
Countries that are still developing experience significant disparities in access to railway services, as these nations also grapple with societal inequality issues that remain unaddressed. In developed countries, railway transportation systems serve as the primary mode of transportation for both passengers and goods. However, in recent years, studies on disparities in developed countries have increased, while literature concerning developing countries remains scarce. Therefore, this study takes place in Thailand, a developing country facing significant population disparities. The objective is to examine factors contributing to these disparities in access to railway transportation systems across cities, using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to identify user disparities. The sample group comprises 1,252 randomly selected railway users from various regions in Thailand, obtained through Stratified Random Sampling. The results reveal seven dimensions of disparities: cultural, spatial, societal, political, knowledge-based, economic, and environmental. The CFA results also highlight cultural disparities as a significant factor in explaining access disparities among railway users. These findings can inform relevant organizations, aiding them in better understanding the actual needs of railway users and aligning railway development plans accordingly. Ultimately, this contributes to policy development aimed at reducing access disparities and fostering a more equitable society. Doi: 10.28991/CEJ-2024-010-03-01 Full Text: PDF